Hermenêutica fenomenológica da experiência originária do cristianismo no pensamento de Martin Heidegger - Gonçalves, Lucas de Lima Cavalcanti (2021)
Just as the history of metaphysics, for Heidegger, is a progressive concealment of the question of the meaning of Being, so the history of Christianity witnesses a growing stiffening of the originary Christian experience. As the Greeks who upon inaugurating the question of Being began to forget it, the first Christian thinkers were led to interpret the living experience of faith as an objectuality capable of being fixed in a dogmatic system. To this dogmatic system came the conceptual frameworks of ancient ontology, so that the imprisonment of the spirit, the element of malleability, in the rigid structure of a totalizing institution was consummated. However, all forgetfulness carries the negative simile of what has been forgotten. Thus, Heidegger proposes forgetfulness as the starting point of remembrance, the symbol as an indication of what does not show itself. The objective of this work is to describe how the phenomenological method, which goes from the forgetfulness of the origin to the origin of forgetfulness, is used by Heidegger in the task of clarifying the originary constitution of the experience of Christianity, as an intimate participation of existence in the event of the crucified god. Then, we analyze the possibilities opened up by phenomenology for a theology understood as a non-objectifying discourse about the experience of faith. Furthermore, as the path to the origin of forgetfulness reveals the fact that at the foundations of the forgetfulness of the origin lies, in view of an improper demand for objectivity, a divorce between concrete life and thought, we seek to show how Heidegger's biographical experience of Christianity led him to a destructive appropriation of the Christian tradition. From there, we investigate how, for him, from the writings of the apostle Paul, two currents sprout to fertilize the soil of Christendom: one poetic-mystical, the other dogmatic-institutional. Seeing in the first, which knew how to preserve the creative power of the divine word, higher possibilities, Heidegger finds in the second the moments in which the spirit still speaks from the silence of its concealment. We consider, then, how this discovery of the spirit latent in dogma provides the reading key to the thought of the great mystics of the Christian tradition, whether they were rejected by the dogmatic-institutional way, like the young Luther, or appropriated by it, like Saint Augustine. Based on a phenomenological interpretation of Christian mysticism, we are then faced not only with the origin of forgetfulness, but with the origin itself as an experience of temporality that constitutes the horizon of the meaning of Being.